Procedimiento Directo en el Código Orgánico Integral Penal, y la Colisión de Derechos Constitucionales - Valdivieso Torres, Andrea Vanessa (2018)
Given that the Criminal Law within the Ecuadorian Legislation has been in constant change, it is necessary to remedy the diverse controversies that arise from this, guaranteeing as it is indicated by the Constitution of the Republic of Ecuador as a constitutional country of Rights.qq Guarantee an adequate defense with sufficient time, it is a Right and a Constitutional Guarantee, and as well as Fundamental Right, that is why within the Criminal Law, in the Organic Comprehensive Criminal Code, the Direct Procedure as a new integral procedure to this legal body , it presents us with a process that seeks agility and speed, it is for them that the defense preparation time allowed by this procedure is scarce for a preparation of the adequate defense, which guarantees a correct Due process and that the Legal Security emanated by the Constitution of the Republic of Ecuador. The Ecuadorian Legislation must ensure compliance with the rights issued in current legislation, given that ensuring an adequate and timely defense becomes an essential right in any process, that is why not only seeking speed, concentration and economy process within a process, to speak of an agile justification, but should look for a justified effective and fair, ensuring that it takes a correct due process and a legal security, since a person can not remain in this of defenselessness for a inadequate defense due to a short preparation time. 5 It is for them that the present investigation seeks to demonstrate that the Direct Procedure, within the Comprehensive Criminal Organic Code, the defense preparation time is scarce and allows a collision of Constitutional Rights, given that the term indicated by this Process, would be insufficient at the moment of exercising a correct defense, since time does not allow adequate preparation.